Terjebak dalam Satu Ukuran untuk Semua: Studi Kasus Tentang Ketidakberagaman Pembelajaran di Kelas X SMA - Angga Dinata (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Using qualitative methods, this study aims to describe the practice of differentiated learning in grade X of high school, identify obstacles faced by teachers, analyze factors that influence the success of implementing differentiated learning from the perspective of Ki Hajar Dewantara's philosophy, and determine the perceptions of teachers and students. The results of the study indicate that efforts to differentiated learning have been made, but there are still obstacles such as lack of understanding of concepts, high workload, and lack of support from the school environment. The success of implementing differentiated learning is influenced by how far teachers live the values ​​of humanity and their ability to make students independent. Teachers' and students' perceptions of differentiated learning vary, but generally show great potential. This study concludes that differentiated learning is an approach that is relevant to Indonesian educational values, but requires stronger support from various parties.